Hanging Clothes on Wire and Its Association with Malaria Incidence in Batubara, North Sumatera - Budi Junarman Sinaga; Rahayu Lubis; Erna Mutiara (Masters Program in Public Health, 2019)
Background: The majority of the mosquito and parasite life-history traits that combine to determine malaria transmission intensity are environmental depen-dent. Earlier evidence suggests that certain malaria vectors can spend large parts of their adult life resting indoors. This study aimed to examine the practice of hanging clothes on wire and its association with malaria incidence in Batubara, North Sumatera. Subjects and Method: This was a case control study conducted in Batubara, North Sumatera in March 2018. A total of 176 people aged ? 15 years consisting of 88 cases of malaria and 88 controls were selected for this study. The dependent variable was malaria incidence. The independent variable was hanging clothes on wire. The data were collected by questionnaire and analyzed by a logistic regression. Results: Hanging clothes on wire was associated with an increased risk of malaria (OR= 3.33; 95% CI= 1.65 to 6.73; p= 0.001). Conclusion: Hanging clothes on wire increases the risk of malaria.Keywords: malaria, hanging clothes, wire.Correspondence: